(untitled) (diségno, 2026)
In architecture, the relationship between form and structure often constitutes a central interpretative node for understanding the meaning of a work. In particular, in Italian Rationalist architecture produced between the two World Wars, this relationship assumes an ideological value of complementarity: form becomes a symbolic expression of power and tradition, supported by a structure –sometimes displayed, sometimes hidden– that acts as a cultural medium in shaping the spaces of propaganda. This interdependent relationship is evident in the narrative-ideological trajectories of exhibition complexes. A prominent example is the Mostra d’Oltremare complex in Naples, with particular attention to the pavilions of the Geographic Sector –most of which have been lost– where the interaction between structure and form creates a rhetorical device aimed at sustaining an image of order and power. This image refers to the rich repertoire of overseas imitation models and classical references, often not immediately recognizable and interpretable only through a careful reading of the underlying formal codes. From this perspective, design assumes a hermeneutic function, aimed at rendering intelligible the original configurative matrices. These are reconstructed through a process of surveying and analyzing historiographical sources and translated into a digital model capable of revealing and reflecting on the relationship between form, constructive logic, spatial organization, and symbolic-functional matrices.